Híbrido de monastrol-H2S : síntese e atividade antiproliferativa contra células de câncer de ovário - Taniris Cafiero Braga (2015)
Cancer represents one of the mayor causes of death in the world. According to OMS, this illness has been responsible for 8,2 million deaths in 2012, mainly due to the absence of efficient methods and drugs for treatment. Thus, it is necessary to develop new potential antitumor compounds Among these malignancy, the ovarian cancer isresponsible by high mortality, because the diagnosis usually is late and existing treatment, it is often not efficient. In the search for alternative treatment could be mentioned monastrol and ADTOH. Monastrol is a recognized Eg5 enzyme inhibitor that prevents cells to complete the cell division cycle. ADTOH is a compound recognized for releasing H2S in small doses in biological media and shows itself as a promising drugfor inflammation therapy. Motivated by these compounds peculiar effects this study esis and evaluation of hybrid of monastrol-H2S produced from the coupling between the acid monastrol derivative and the ADTOH with a global yield of 0,4%. There is not any report of the synthesis as well about antiproliferative properties of this hybrid. The antiproliferative trials were accomplished in human ovarian tumor lines TOV-21G (ATCC).The antiproliferative test in TOV-21G cells showed that monastrol hybrid had cytotoxic properties more similarly to monastrol than to ADTOH. It was confirmed that the TOV-21G viability is not dose dependent in the evaluated concentrations (1 pg/mL, 5 pg/mL, 10 pg/mL and 15 pg/mL). In addition, it will be necessary another trials with different concentrations and a bigger tumor panel for antitumor activity's hybrid analysis.